1997
DOI: 10.1002/(sici)1520-6327(1997)34:3<347::aid-arch8>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Separation by FPLC chromatofocusing of UDP-glucosyltransferases from three developmental stages ofDrosophila melanogaster

Abstract: Variation of UDP‐glucosyltransferase activity, during Drosophila melanogaster development, was analyzed. The endogenous metabolite xanthurenic acid and the xenobiotic compounds 1‐naphthol and 2‐naphthol were used as substrates. Developmentally regulated differences were observed for the three substrates, suggesting the presence of UDP‐glucosyltransferase isoenzymes. This was further confirmed by FPLC chromatofocusing on a Mono P column: seven peaks of UDP‐glucosyltransferase activity (pHs: ≥6.3, 5.8, 5.5, 4.9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Insect UGTs, on the other hand, are implicated in the detoxifications of insecticides [34]. UGTs activity was highly expressed in the larval and adult stages in D. melanogaster , and correlated with increased detoxification capability [61]. In Bombyx mori , expressed BmUGT1 can conjugate a wide range of substrates including flavonoids, coumarins and other phenolic compounds, suggesting a role of UGTs in detoxification processes [62].…”
Section: Discussionmentioning
confidence: 99%
“…Insect UGTs, on the other hand, are implicated in the detoxifications of insecticides [34]. UGTs activity was highly expressed in the larval and adult stages in D. melanogaster , and correlated with increased detoxification capability [61]. In Bombyx mori , expressed BmUGT1 can conjugate a wide range of substrates including flavonoids, coumarins and other phenolic compounds, suggesting a role of UGTs in detoxification processes [62].…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In Drosophila melanogaster, variations in the UDP-glucosyltransferase activity have been analyzed by using the xenobiotic compounds, 1-naphtol and 2-naphtol. 29) In this study, however, we showed that M. separata larvae were able to transform such Bxs such as DIMBOA, HMBOA and MBOA to O-glucosides and methoxy glucoside carbamate as detoxification products. Although the total recovery ratio was approximately 10% based on the administered amount of DIMBOA in the feeding experiment, these findings might be a good example showing that UDP-glucosyltransferases play an important role in the detoxification of plant allelochemicals by insects, and provide a wider range of detoxification facilities to circumvent the chemical defenses of host plants than we expected.…”
Section: Discussionmentioning
confidence: 99%
“…The UDP-sugar donor may be UDP-glucuronic acid (UDP-GlcA), UDP-galactose (UDP-gal), UDPglucose (UDP-Glc), or UDP-xylose. It has been established that vertebrate UDP-glycosyltransferases preferentially use UDP-GlcA (Bock, 2003), whereas insect and plant UDP-glycosyltransferases typically use UDP-Glc (Ahmad and Forgash, 1976;Rausell et al, 1997;Hansen et al, 2003). This high selectivity for the common donor substrate could be related to the highly conserved donorbinding domain of the enzymes and has been found to be determined by critical amino acid residues in the catalytic domain in some UDP-glycosyltransferases.…”
mentioning
confidence: 99%